Reconstruction of fire frequency and burned areas around Yaksha village, Komi republic, Russia - Drobyshev, Igor (Swedish University of Agricultural Sciences, 2022)
Dendrochronological reconstruction of the fire frequency and the area burned in the pine-dominated forests in the vicinity of the Yaksha village, southern Komi republic, Russia. The reconstruction is based on dendrochronological dating of fire scars on live and dead pine trees. The reconstruction extends from approximately 1400s to 2016 and is done with annual resolution. The complete presentation of sampling protocol and data analyses could be found in "Climate drove the fire cycle and humans influenced fire occurrence in the East European boreal forest", Ryzhkova et al, Ecological Monographs, 2022.

The dataset contains two reconstructions: the decadal fire occurrence in the study area and the annual area burned. The reconstruction is based on dendrochronological dating of fire scars on live and dead pine (Pinus sylvestris) trees. In the chronology, the data label points to the start of the decade in question. For example, label 1540 refers to the decade 1540-1549. The complete presentation of sampling protocol and data analyses could be found in "Climate drove the fire cycle and humans influenced fire occurrence in the East European boreal forest", Ryzhkova et al, Ecological Monographs, 2022.

Dendrokronologisk rekonstruktion av brandfrekvens och bränd yta i tallskogar i södra republik Komi (område i närheten av by Yaksha), Ryssland. Den årliga rekonstruktion bygger på datering av brandljud i levande och döda tallar och sträcker sig från 1400 till 2016. Den fullständiga provtagningsprotokoll och resultatanalys finns i artikeln "Climate drove the fire cycle and humans influenced fire occurrence in the East European boreal forest", Ryzhkova et al, Ecological Monographs, 2022.

Dataset innehåller två rekonstruktioner: decadal förekomst av skogsbränder och årliga brända areal. Rekonstruktionen bygger på dendrokronologisk datering av brandljud på levande och död ved av tall (Pinus sylvestris). I kronologin pekar markering på början av decennium. Till exempel, markering (label) 1540 pekar på perioden 1540-1549. Den fullständiga provtagningsprotokoll och resultatanalys finns i artikeln "Climate drove the fire cycle and humans influenced fire occurrence in the East European boreal forest", Ryzhkova et al, Ecological Monographs, 2022.
Rekonstruktion av skogbrandsfrekvens och bränd areal i Yaksha by, Republik Komi, Ryssland
Keywords: forest history; skogshistoria; boreal ecology; boreal ekologi; forest use; skogsbruk; Pinus sylvestris; Natural Sciences; Naturvetenskap; Biological Sciences; Biologi